2012
DOI: 10.1155/2012/358184
|View full text |Cite
|
Sign up to set email alerts
|

MCP-1-Induced Histamine Release from Mast Cells Is Associated with Development of Interstitial Cystitis/Bladder Pain Syndrome in Rat Models

Abstract: Objective. Interstitial cystitis/bladder pain syndrome (IC/BPS) is characterized by overexpression of monocyte chemoattractant protein-1 (MCP-1) in bladder tissues and induction of mast cell (MC) degranulation. This study was undertaken to explore the mechanism of action of MCP-1 in the development of IC/BPS. Methods. A rat model of IC/BPS was developed by perfusing bladders of nine SPF- grade female Sprague-Dawley rats with protamine sulfate and lipopolysaccharide (PS+LPS). MCP-1 and histamine levels in bladd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 22 publications
0
36
0
Order By: Relevance
“…Increased histidine level leads to increase of histamine level in blood, brain and possibly bladder, suggesting the possibility that histidine may have many other possible functions affecting human bladder sensory system. Previous work using IC rat model demonstrated that overexpression of monocyte chemo-attractant protein-1 (MCP-1) in bladder tissues contributes histamine production and IC12. More recently, findings from animal model suggest that mast cell-derived histamine mediates IC-associated pain.…”
Section: Discussionmentioning
confidence: 99%
“…Increased histidine level leads to increase of histamine level in blood, brain and possibly bladder, suggesting the possibility that histidine may have many other possible functions affecting human bladder sensory system. Previous work using IC rat model demonstrated that overexpression of monocyte chemo-attractant protein-1 (MCP-1) in bladder tissues contributes histamine production and IC12. More recently, findings from animal model suggest that mast cell-derived histamine mediates IC-associated pain.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotactic cytokines, chemokine ligands 2 and 3 (CCL2 and CCL3), have been identified as important mediators in pelvic pain associated with a murine model of experimental prostatitis [44]. CCL2 can also induce histamine release that is subsequently associated with the development of cystitis-related pain in rats [45]. …”
Section: Mast Cells In Pre-clinical Models Of Inflammatory and Chrmentioning
confidence: 99%
“…References BPS/interstitial cystitis Alteration related to mast cells Increase of mast cell density in urinary bladder -detrusor muscle, submucous layer of bladder, urinary bladder epithelium [20][21][22][23][24][25] 60% increase of histamine tissue level in bioptic tissues of human bladder versus control tissue [20,21] Increase of urinary mast cell markers (histamine, methylhistamine, tryptase, NGF, IL-6, IL-8, YKL-40, etc.) [25][26][27][28][29] Alteration of nerve terminals Increase in nerve fiber density as evaluated by SP and TRPV1 immunohistochemical assessment and increased mRNANK1 receptor expression [22] IBS Alteration related to mast cells Increase of mast cell density in bioptic intestinal tissues [30][31][32][33] Increase of histamine, NGF, tryptase levels measured in bioptic tissues of human colon [31][32][33][34] Alteration of nerve terminals Increased nerve fiber density as evaluated by SP and TRPV1 immunohistochemical assessment.…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28][29] Alteration of nerve terminals Increase in nerve fiber density as evaluated by SP and TRPV1 immunohistochemical assessment and increased mRNANK1 receptor expression [22] IBS Alteration related to mast cells Increase of mast cell density in bioptic intestinal tissues [30][31][32][33] Increase of histamine, NGF, tryptase levels measured in bioptic tissues of human colon [31][32][33][34] Alteration of nerve terminals Increased nerve fiber density as evaluated by SP and TRPV1 immunohistochemical assessment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation